Boiling-resistant solvent-free laminating adhesive and preparation method thereof
By reasonably matching catalysts and using specific polymers in solvent-free composite film glue, boil-resistant solvent-free composite film glue is prepared, which solves the problem of insufficient performance of existing glue, achieves efficient and environmentally friendly adhesive performance, and improves production efficiency and product adhesion.
Patent Information
- Application Number
- CN202411944698.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-18
AI Technical Summary
The existing solvent-free composite film glue has problems such as high viscosity, low strength, high maturation temperature and slow strength in terms of performance, which is difficult to meet the demand for high-performance glue in the chemical industry.
By reasonably combining catalysts and combining polyether polyols and polyester polyols, a boil-resistant solvent-free composite film glue is prepared, which has the characteristics of low viscosity, high strength, low maturation temperature and rapid strength.
It achieves good adhesion to film materials such as PET, PE, aluminum foil, etc., shortens the maturation time of film materials, improves bag making speed and production line efficiency, reduces production costs, and ensures the environmental protection and performance of the product.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane laminating adhesives, and in particular relates to a boiling-resistant solvent-free laminating adhesive and a preparation method thereof. Background Art
[0002] In the manufacturing industry, traditional solvent-based glues can cause problems such as the emission of volatile organic compounds that harm the environment and human health during use. Solvent-free laminating adhesives, with their environmentally friendly and efficient characteristics, use non-volatile organic compounds as basic raw materials, which can not only meet the product's bonding performance requirements, but also reduce environmental pollution, meet the modern society's requirements for green environmental protection, and contribute to environmental protection and sustainable development. Solvent-free laminating adhesives are attracting more and more attention and applications, and are gradually becoming a new favorite.
[0003] Solvent-free laminating adhesive plays an important role in the fields of automobile manufacturing, architectural decoration, packaging and printing, and has a broad application prospect. For example, in automobile manufacturing, solvent-free laminating adhesive can be used for bonding of automobile interior parts, which can not only improve the firmness of bonding, but also effectively reduce the emission of volatile organic compounds, providing technical support for the sustainable development of the automobile manufacturing industry.
[0004] With the continuous advancement and innovation of technology, the requirements for solvent-free laminating adhesives are getting higher and higher. It is necessary to further improve the performance of solvent-free laminating adhesives and provide a water-boiling-resistant solvent-free laminating adhesive with excellent properties such as low viscosity, high strength, low aging temperature, and very fast strength development, so as to inject new vitality and impetus into the development of the chemical industry. Summary of the invention
[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides a boiling-resistant solvent-free laminating adhesive and a preparation method thereof. The specific technical scheme is as follows:
[0006] The first object of the present invention is to provide a boiling-resistant solvent-free laminating adhesive, comprising component A and component B, measured by weight:
[0007] Component A:
[0008] Polyether polyol A 25-55 parts; Polyether polyol B 5-25 parts; Polyester polyol A 3-10 parts; Isocyanate 20-55 parts;
[0009] The functionality of the polyether polyol A is 2, and the hydroxyl value is 54.5-57.5 mgKOH / g; the functionality of the polyether polyol B is 3, and the hydroxyl value is 26.5-29.5 mgKOH / g; the functionality of the polyester polyol A is 2, and the hydroxyl value is 54-58 mgKOH / g;
[0010] Component B:
[0011] Polyether polyol C 10-20 parts; polyether polyol D 10-20 parts; polyether polyol E 10-30 parts; polyester polyol B 5-35 parts; coupling agent 0.5-3 parts; catalyst 0.001-1 parts;
[0012] The functionality of the polyether polyol C is 2, and the hydroxyl value is 109-115 mgKOH / g; the functionality of the polyether polyol D is 3, and the hydroxyl value is 163-173 mgKOH / g; the functionality of the polyether polyol E is 2, and the hydroxyl value is 270-290 mgKOH / g; the functionality of the polyester polyol B is 2, and the hydroxyl value is 120-130 mgKOH / g;
[0013] The weight ratio of the component A to the component B is 1:0.5-1.25.
[0014] Furthermore, the molecular weight of the polyether polyol A is one of 400, 1000, 2000, and 4000, preferably 2000 molecular weight, such as DL-2000D of Shandong Bluestar Dongda Co., Ltd.
[0015] Furthermore, the molecular weight of the polyether polyol B is one of 500, 700, 1000, 3000 and 6000, preferably 6000, such as EP-3600 of Shandong Bluestar Dongda Co., Ltd.
[0016] Furthermore, the molecular weight of the polyether polyol C is one of 400, 1000, 2000, and 4000, preferably 1000, such as DL-1000D produced by Shandong Bluestar Dongda Co., Ltd.
[0017] Furthermore, the molecular weight of the polyether polyol D is one of 500, 700, 1000, 3000, and 6000, preferably 1000, such as MN-1000 produced by Shandong Bluestar Dongda Co., Ltd.
[0018] Furthermore, the molecular weight of the polyether polyol E is one of 400, 1000, 2000 and 4000, preferably 400, such as DL-400 produced by Shandong Bluestar Dongda Co., Ltd.
[0019] Furthermore, the molecular weight of the polyester polyol A is one of 900, 1000, 2000 and 4000, preferably 2000, such as XCP-2000D of Asahikawa Chemical (Suzhou) Co., Ltd.
[0020] Furthermore, the molecular weight of the polyester polyol B is one of 900, 1000, 2000 and 4000, preferably 900, such as XCP-900ED of Asahikawa Chemical (Suzhou) Co., Ltd.
[0021] Furthermore, the coupling agent is a silane coupling agent, preferably KBM-403 produced by Shin-Etsu Chemical Co., Ltd.
[0022] Furthermore, the catalyst is one or more of an organic sodium catalyst, a potassium catalyst or a rare earth catalyst, preferably a rare earth catalyst and an organic sodium / potassium catalyst are mixed for use, and the mass ratio of the rare earth catalyst to the organic sodium / potassium catalyst is (5-9):1.
[0023] The solvent-free laminating adhesive of the present invention can effectively shorten the room temperature film material maturation time, improve the bag making speed, speed up the efficiency of the entire production line, and reduce the production cost from the process end through the reasonable combination of catalysts. In addition, this catalyst combination has no obvious catalytic effect on water and isocyanate groups, and is not easy to foam after coating, which ensures the appearance and performance of the product. The rare earth catalyst brings better hydrolysis resistance to the colloid and is more resistant to boiling. At the same time, this catalyst combination can make the glue have a viscosity-time curve that is more in line with the production process, with the characteristics of small viscosity growth in the early stage and fast strength increase in the later stage.
[0024] Furthermore, the isocyanate is diphenylmethane-4,4'-diisocyanate.
[0025] Furthermore, the isocyanate is one or more of MDI-50, MDI-100, polymeric MDI and liquefied MDI, preferably MDI-50 and / or MDI-100.
[0026] The second object of the present invention is to provide a method for preparing the above-mentioned boiling-resistant solvent-free laminating adhesive, comprising the following steps:
[0027] Component A laminating adhesive: Mix the materials of component A, slowly heat to 60-100°C in a protective gas atmosphere, stir and react for 1-3 hours to form a prepolymer;
[0028] B component laminating adhesive: degassing and mixing the B component polyether polyol C, polyether polyol D, polyether polyol E and polyester polyol B evenly, then adding coupling agent and catalyst to degas and mix evenly, and packaging and storing separately.
[0029] The laminating adhesive of the present invention recommends the following parameters:
[0030] Recommended glue amount 1.0-3.0g / ㎡; feeding unit 38-40℃; transmission roller 35-40℃; metering roller 35-40℃; coating roller 35-45℃; compounding temperature 35-40℃; machine speed 0-500m / min. Specific parameters can be adjusted according to different situations.
[0031] The beneficial effects of the present invention are:
[0032] The boiling-resistant solvent-free laminating adhesive provided by the present invention has good adhesion to film materials of various materials such as PET, PE, and aluminum foil, and the gluing process temperature is low. It can be cured at room temperature for 12 hours and the bag can be made for 24 hours to reach the expected peeling strength. The cost is comparable to that of solvent-based laminating adhesives, and it is environmentally friendly and pollution-free. It is a boiling-resistant solvent-free laminating adhesive with excellent properties such as low viscosity, high strength, low curing temperature, and very fast strength development. DETAILED DESCRIPTION
[0033] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0034] Polyether polyol A is DL-2000D from Shandong Bluestar Dongda Co., Ltd.;
[0035] Polyether polyol B is EP-3600 from Shandong Bluestar Dongda Co., Ltd.;
[0036] Polyether polyol C is DL-1000D from Shandong Bluestar Dongda Co., Ltd.;
[0037] Polyether polyol D is MN-1000 from Shandong Bluestar Dongda Co., Ltd.;
[0038] Polyether polyol E is DL-400 from Shandong Bluestar Dongda Co., Ltd.;
[0039] Polyester polyol A is XCP-2000D from Asahikawa Chemical (Suzhou) Co., Ltd.;
[0040] Polyester polyol B is XCP-900ED produced by Asahikawa Chemical (Suzhou) Co., Ltd.;
[0041] The coupling agent is KH-560;
[0042] The catalyst is a mixture of a rare earth catalyst and an organic sodium salt catalyst;
[0043] The above components are used in the preparation of the laminating adhesives of the following examples and comparative examples.
[0044] Embodiment 1:
[0045] A preparation method of a boiling-resistant solvent-free laminating adhesive comprises the following steps:
[0046] Component A laminating adhesive: Add 75.0g DL-2000D, 15.0g EP-3600, 20.0g XCP-2000D, and 110.0g MDI-50 into a three-necked flask equipped with a stirring paddle, pass nitrogen gas, slowly heat to 80°C, stir and react for 2h to obtain the compound;
[0047] Component B laminating adhesive: first add 20.0g DL-1000D, 40.0g MN-1000, 20.0g DL-400 and 20.0g XCP-900ED into a mixing tank, deaerate and mix evenly, then add 1.0g KH-560 and a mixture of 0.007g rare earth catalyst and 0.001g organic sodium salt catalyst (the mass ratio of rare earth catalyst to organic sodium salt catalyst is 7:1), deaerate and mix evenly to obtain component B laminating adhesive.
[0048] When in use, the two components with an R value (molar ratio of isocyanate group to hydroxyl group) of 1.35 are mixed evenly and then coated, and cured at room temperature or heated to a temperature below 80°C. The curing temperature in this embodiment is 25°C.
[0049] Embodiment 2:
[0050] A preparation method of a boiling-resistant solvent-free laminating adhesive comprises the following steps:
[0051] Component A laminating adhesive: Add 70.0g DL-2000D, 20.0g EP-3600, 20.0g XCP-2000D, and 110.0g MDI-50 into a three-necked flask equipped with a stirring paddle, pass nitrogen gas, slowly heat to 80°C, stir and react for 2h to obtain the compound;
[0052] Component B laminating adhesive: first add 30.0g DL-1000D, 30.0g MN-1000, 20.0g DL-400 and 20.0g XCP-900ED into a mixing tank, deaerate and mix evenly, then add a mixture of 1.0g KH-560, 0.007g rare earth catalyst and 0.001g organic sodium salt catalyst, deaerate and mix evenly to obtain component B laminating adhesive.
[0053] When in use, the two components with an R value of 1.35 are mixed evenly and then applied, and then cured at room temperature or heated to a temperature below 80°C. The curing temperature in this embodiment is 25°C.
[0054] Embodiment 3:
[0055] A preparation method of a boiling-resistant solvent-free laminating adhesive comprises the following steps:
[0056] Component A laminating adhesive: Add 80.0g DL-2000D, 10.0g EP-3600, 20.0g XCP-2000D, and 110.0g MDI-50 into a three-necked flask equipped with a stirring paddle, pass nitrogen gas, slowly heat to 80°C, stir and react for 2h to obtain the compound;
[0057] Component B laminating adhesive: first add 20.0g DL-1000D, 30.0g MN-1000, 30.0g DL-400 and 20.0g XCP-900ED into a mixing tank, deaerate and mix evenly, then add a mixture of 1.0g KH-560, 0.007g rare earth catalyst and 0.001g organic sodium salt catalyst, deaerate and mix evenly to obtain component B laminating adhesive.
[0058] When in use, the two components with an R value of 1.35 are mixed evenly and then applied, and then cured at room temperature or heated to a temperature below 80°C. The curing temperature in this embodiment is 25°C.
[0059] Comparative Example 1
[0060] A preparation method of a solvent-free laminating adhesive comprises the following steps:
[0061] Component A laminating adhesive: Add 75.0g DL-2000D, 15.0g EP-3600, 20.0g XCP-2000D, and 110.0g MDI-50 into a three-necked flask equipped with a stirring paddle, pass nitrogen gas, slowly heat to 80°C, stir and react for 2h to obtain the compound;
[0062] Component B laminating adhesive: first add 20.0g DL-1000D, 40.0g MN-1000, 20.0g DL-400 and 20.0g XCP-900ED into a mixing tank, deaerate and mix evenly, then add 1.0g KH-560 and 0.08g organic sodium salt catalyst, deaerate and mix evenly to obtain the laminating adhesive.
[0063] When in use, the two components with an R value of 1.35 are mixed evenly and then applied, and then cured at room temperature or heated to a temperature below 80°C. The curing temperature in this embodiment is 25°C.
[0064] Comparative Example 2
[0065] A preparation method of a solvent-free laminating adhesive comprises the following steps:
[0066] Component A laminating adhesive: Add 75.0g DL-2000D, 15.0g EP-3600, 20.0g XCP-2000D, and 110.0g MDI-50 into a three-necked flask equipped with a stirring paddle, pass nitrogen gas, slowly heat to 80°C, stir and react for 2h to obtain the compound;
[0067] Component B laminating adhesive: first add 20.0g DL-1000D, 40.0g MN-1000, 20.0g DL-400 and 20.0g XCP-900ED into a mixing tank, deaerate and mix evenly, then add 1.0g KH-560 and 0.008g organic sodium salt catalyst, deaerate and mix evenly to obtain the laminating adhesive.
[0068] When in use, the two components with an R value of 1.35 are mixed evenly and then applied, and then cured at room temperature or heated to a temperature below 80°C. The curing temperature in this embodiment is 25°C.
[0069] Comparative Example 3
[0070] A preparation method of a solvent-free laminating adhesive comprises the following steps:
[0071] Component A laminating adhesive: Add 80.0g DL-2000D, 10.0g EP-3600, 20.0g XCP-2000D, and 110.0g MDI-50 into a three-necked flask equipped with a stirring paddle, pass nitrogen gas, slowly heat to 80°C, stir and react for 2h to obtain the compound;
[0072] Component B laminating adhesive: first add 30.0g DL-1000D, 10.0g MN-1000, 40.0g DL-400 and 20.0g XCP-900ED into a mixing tank, deaerate and mix evenly, then add a mixture of 1.0g KH-560, 0.007g rare earth catalyst and 0.001g organic sodium salt catalyst, deaerate and mix evenly to obtain the laminating adhesive.
[0073] When in use, the two components with an R value of 1.35 are mixed evenly and then applied, and then cured at room temperature or heated to a temperature below 80°C. The curing temperature in this embodiment is 25°C.
[0074] The obtained laminating adhesives of Examples 1-3 and Comparative Examples 1-2 were tested and compared repeatedly. The results are shown in Table 1. The test curing conditions in the table below are 25°C, 12h, T-type peeling CHS300 300mm / min (25°C / 50%RH), and the strength unit is N / 15mm. The results are shown in Table 1.
[0075] Table 1. Test results of laminating adhesive performance of Examples 1-3 and Comparative Example 1
[0076] Test Structure Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 PET / PE 4.21 4.44 4.18 3.01 2.02 3.71 OPP / CPP 2.18 2.34 2.01 1.52 1.12 1.82 PA / PE 3.96 4.01 3.88 2.86 1.76 3.86 PET / CPP 3.04 3.23 3.11 1.78 1.23 2.58 PET / AL 4.76 4.88 4.58 3.04 2.12 4.04 AL / PE 3.58 3.85 3.47 1.89 1.37 2.89 AL / RCPP 3.77 3.97 3.55 1.77 1.37 3.17 OPP / VMPET 2.43 2.37 2.11 1.32 1.13 1.82 VMPET / PE 3.92 3.73 3.93 1.36 1.25 3.36
[0077] The test curing conditions are 25°C, 30h, T-peel CHS300 300mm / min (25°C / 50%RH), the strength unit is N / 15mm, and the results are shown in Table 2.
[0078] Table 2. Test results of laminating adhesive performance of Examples 1-3 and Comparative Example 1
[0079] Test Structure Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 PET / PE 5.73 6.12 6.18 5.01 3.23 5.13 OPP / CPP 2.88 2.94 2.56 2.34 1.05 2.02 PA / PE 5.36 5.51 5.88 4.77 3.11 4.66 PET / CPP 4.32 4.44 4.54 3.68 2.13 3.77 PET / AL 6.46 6.56 6.34 5.34 4.03 5.34 AL / PE 5.26 5.45 5.43 4.84 3.01 4.78 AL / RCPP 5.77 5.45 5.35 4.67 3.45 4.88 OPP / VMPET 2.87 2.91 2.77 2.02 0.99 2.56 VMPET / PE 6.20 6.35 6.24 4.78 3.33 5.67
[0080] After curing at 25℃ for 7 days, PET / AL / PA / RCPP were subjected to 121℃ cooking test, and there was no significant change in appearance and peel strength, with no obvious difference.
[0081] Through the above comparative test, it is found that there is a significant difference in the strength of 12 hours and 30 hours, especially the 30h peel strength of comparative example 1 is smaller than that of the embodiment of the present invention, which is slightly lower, proving that the catalyst combination of this invention can be matured faster. In the 12h peel strength test, the strength of comparative example 2 is significantly lower than that of the embodiment, and does not meet the bag making conditions. The catalyst combination of the present invention meets the process beat while ensuring adhesion, and also meets the conditions of 12h bag making, which can greatly improve the production line efficiency and create significant economic benefits. Comparative example 3 is lower than the embodiment in 30h strength compared with the embodiment, and the polyol ratio is better with the embodiment.
[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A boiling-resistant solvent-free laminating adhesive, characterized in that: Including component A and component B, by weight: Component A: Polyether polyol A 25-55 parts; Polyether polyol B 5-25 parts; Polyester polyol A 3-10 parts; Isocyanate 20-55 parts; The functionality of the polyether polyol A is 2, and the hydroxyl value is 54.5-57.5 mgKOH / g; the functionality of the polyether polyol B is 3, and the hydroxyl value is 26.5-29.5 mgKOH / g; the functionality of the polyester polyol A is 2, and the hydroxyl value is 54-58 mgKOH / g; Component B: Polyether polyol C 10-20 parts; polyether polyol D 10-20 parts; polyether polyol E 10-30 parts; polyester polyol B 5-35 parts; coupling agent 0.5-3 parts; catalyst 0.001-1 parts; The functionality of the polyether polyol C is 2, and the hydroxyl value is 109-115 mgKOH / g; the functionality of the polyether polyol D is 3, and the hydroxyl value is 163-173 mgKOH / g; the functionality of the polyether polyol E is 2, and the hydroxyl value is 270-290 mgKOH / g; the functionality of the polyester polyol B is 2, and the hydroxyl value is 120-130 mgKOH / g; The weight ratio of the component A to the component B is 1:0.5-1.
25.
2. The boiling-resistant solvent-free laminating adhesive according to claim 1, characterized in that: The polyether polyol A has a molecular weight of 400, 1000, 2000, and 4000; the polyether polyol B has a molecular weight of 500, 700, 1000, 3000, and 6000; the polyether polyol C has a molecular weight of 400, 1000, 2000, and 4000; the polyether polyol D has a molecular weight of 500, 700, 1000, 3000, and 6000; and the polyether polyol E has a molecular weight of 400, 1000, 2000, and 4000.
3. The boiling-resistant solvent-free laminating adhesive according to claim 1, characterized in that: The polyester polyol A has a molecular weight of 900, 1000, 2000, and 4000; the polyester polyol B has a molecular weight of 900, 1000, 2000, and 4000.
4. The boiling-resistant solvent-free laminating adhesive according to claim 1, characterized in that: The coupling agent is a silane coupling agent.
5. The boiling-resistant solvent-free laminating adhesive according to claim 1, characterized in that: The catalyst is one or more of an organic sodium catalyst, an organic potassium catalyst or a rare earth catalyst.
6. The boiling-resistant solvent-free laminating adhesive according to claim 5, characterized in that: The catalyst is a mixture of a rare earth catalyst and an organic sodium / potassium catalyst, and the mass ratio of the rare earth catalyst to the organic sodium / potassium catalyst is (5-9):
1.
7. The boiling-resistant solvent-free laminating adhesive according to claim 1, characterized in that: The isocyanate is diphenylmethane-4,4'-diisocyanate.
8. The boiling-resistant solvent-free laminating adhesive according to claim 7, characterized in that: The isocyanate is one or more of MDI-50, MDI-100, polymeric MDI and liquefied MDI.
9. A method for preparing the boiling-resistant solvent-free laminating adhesive according to claims 1 to 8, characterized in that: The following steps are involved: Component A laminating adhesive: Mix the materials of component A, slowly heat to 60-100°C in a protective gas atmosphere, stir and react for 1-3 hours to form a prepolymer; Component B laminating adhesive: degassing and mixing the component B polyether polyol C, polyether polyol D, polyether polyol E and polyester polyol B evenly, then adding coupling agent and catalyst to degas and mix evenly, and packaging and storing separately.
Citation Information
Patent Citations
Method for producing a multi-layer moulded part
EP2230061A2
Cited By
A polyisocyanate composition, process for its preparation and use thereof
CN122705845A